Assessment of Body Mass Index (BMI) and General Health Status of Male Auto-Rickshaw Drivers in Garia, Kolkata (Global Journal of Medical Research, 2022)
Background In India auto-rickshaw is one of the main modes of public transport in urban and semi-urban areas however auto-rickshaw drivers often suffer from various nutritional deficiencies Objective The objective of this work is to assess the body mass index BMI and the general health status of the auto-rickshaw drivers of the Garia Southern Avenue auto-rickshaw stand in Kolkata Method To achieve this objective a cross-sectional study has been undertaken whereby data have been collected in February-July 2018 regarding duration of work nature of addiction ownership pattern general clinical status BMI and body fat percentage of 157 male auto-rickshaw drivers attached to the aforesaid stand and belonging to the age-group of 18-55 years Subsequently the binomial test has been conducted at 5 level of significance
Keywords: auto-rickshaw driver; Kolkata; body mass index; health status; binomial test; cross-sectional study